THE PETRI NET SIMULATION OF TEMPEH PROCESSING PROSESS WITH FOUR OPERATORS - Murdianto, Deny (Department of Mathematics Education , University of Jember, 2022)
The model obtained in this study is expected to be able to describe the dynamics of the resources and processing of soybeans into tempeh. An understanding of the tempeh production process is obtained from direct observation and also from appropriate references. Furthermore, a petri net model and simulation of the tempeh production process was made with several assumptions that have been adjusted to the results of observations in the field. Obtained a petri net consisting of 14 places and 10 transitions. From the simulation results, must be reachable to reach the final state that has been determined with several assumptions.